Improved Progression-Free Survival in Irinotecan-Treated Metastatic Colorectal Cancer Patients Carrying the HNF1A Coding Variant p.I27L - Labriet, Adrien; De Mattia, Elena; Cecchin, Erika; Lévesque, Éric; Jonker, Derek; Couture, Félix; Buonadonna, Angela; D’Andrea, Mario; Villeneuve, Lyne; Toffoli, Giuseppe; Guillemette, Chantal (Frontiers in Pharmacology, 2017)
Hepatocyte nuclear factor 1-alpha (HNF1A) is a liver-enriched transcription factor that plays a key role in many aspects of hepatic function including detoxification processes. We examined whether HNF1A polymorphisms are associated with clinical outcomes in two independent cohorts combining 417 European ancestry patients with metastatic colorectal cancer (mCRC) treated with irinotecan-based chemotherapy. The intronic rs2244608A>G marker was predictive of an improved progression-free survival with a trend in the Canadian cohort and reaching significance in the Italian cohort, with hazard ratios (HR) of 0.74 and 0.72, P = 0.076 and 0.038, respectively. A strong association between rs2244608A>G and improved PFS was found in the combined analysis of both cohorts (HR = 0.72; P = 0.002). Consistent with an altered HNF1A function, mCRC carriers of the rs2244608G minor allele displayed enhanced drug exposure by 45% (P = 0.032) compared to non-carriers. In Caucasians, rs2244608A>G is in strong linkage with the coding variant rs1169288c.79A>C (HNF1A p.I27L). In healthy donors, we observed an altered hepatic (ABCC1, P = 0.009, ABCC2, P = 0.048 and CYP3A5, P = 0.001; n = 89) and intestinal (TOP1, P = 0.004; n = 75) gene expression associated with the rs1169288C allele. In addition, the rs1169288C polymorphism could significantly increase the ABCC1 promoter activity by 27% (P = 0.008) and 15% (P = 0.041) in the human kidney HEK293 and the human liver HepG2 cell lines, respectively. Our findings suggest that the HNF1A rs2244608, or the tightly linked functional coding variant p.I27L, might be a potential prognostic marker with irinotecan-based regimens.